Tacrolimus shows adequate efficacy in patients with antiphospholipid antibodies associated thrombocytopenia: a retrospective cohort study - Shi, Yu; Huang, Can; Zhou, Yangzhong; Jiang, Hui; Zhao, Yongqiang; Li, Mengtao; Zeng, Xiaofeng; Zhao, Jiuliang (Clinical and experimental medicine, 2023)
Thrombocytopenia is a common manifestation associated with the presence of antiphospholipid antibodies (aPL). The aim of this study is to investigate the efficacy and safety of tacrolimus treatment in aPL associated thrombocytopenia. This is a single-center retrospective study. Patients who had persistent positive aPL and thrombocytopenia that was treated with tacrolimus were included. A total of 49 patients [38 females (77.6%)] were enrolled from Nov 2013 to Apr 2022 with a median treatment duration of 22 months. Seventeen fulfilled classification criteria of antiphospholipid syndrome (APS), 18 systemic lupus erythematosus (SLE). The median age of study patients was 37 years (IQR 31, 48). Forty-three (87.8%) patients were on concomitant use of glucocorticoids, 6 on tacrolimus monotherapy. The overall response rate in this cohort was 85.7% ( n = 42), including 49% of complete responses ( n = 24). The median time to achieve a response was 3 months. Nine (18.4%) patients with overall response experienced a loss of response. The response rate during follow-up in patients with monotherapy was noninferior. Patients with positive antinuclear antibody (ANA) showed the tendency of maintaining response ( p = 0.028). The 19 patients who were on medium and high dosage of glucocorticoids (> 15 mg prednisone/d) managed to taper glucocorticoids rapidly. Side effects were reported in 12.2% ( n = 6) of the patients (elevated creatinine, general malaise, elevated liver enzyme). Tacrolimus has adequate efficacy, steroid-sparing effect and is well tolerated for aPL associated thrombocytopenia. Patients with positive ANA might benefit the most from tacrolimus treatment.